RECEPTIVENESS OF INTERNET BANKING BY MALAYSIAN CONSUMERS: THE CASE OF PENANG - T. Ramayah; Muhamad Jantan; Mohd Nasser Mohd Noor; Koay Pei Ling; Razli Che Razak (Asian Academy of Management Journal, 2003)
By adopting a cultural perspective of organizations, and more specifically, using the structural model of culture as a framework, this investigation attempts to discover the underlying structure of reality in mainland Chinese organizations.This study proposes that at the heart of Chinese organizational culture lie three dominant assumptions, namely "the ever hostile environment", "social reality in hierarchical order", and the "self-seeking human being", which relate to the environment, group, and individual respectively. This triad of assumptions not only animates Chinese organizational culture but also constitutes a unifying thread connecting the different components of this culture. The outward manifestations of this mix of organizational assumptions can best be depicted as a clash of two cultural elitist forces – power and role culture. While power culture is characterized by bonds of personal patronage, personal connections, and displays of personal authority and subservience, role culture emphasizes institutional authority, the rule of law, and meritocracy. The former is presently in command of organizational leadership while the latter has emerged principally as a response to the excesses of the former. Interestingly, although the two cultures are supported by two different sets of values, they rest on a common set of organizational assumptions.